Inovasi Usaha Mikro Kecil Menengah (UMKM) pada Kue Semprit dengan Parsimoni Untung Selangit Guna Pemulihan Ekonomi Nasional Pasca Pandemi - Hanifah Aulia Kusuma (Madani: Jurnal Pengabdian Ilmiah, 2023)
Abstract: Syringe cake, a delectable pastry crafted from a mixture of flour, fat, powdered sugar, and eggs, has captured the taste buds of many. This research delves into the world of small-scale bakeries producing syringe cakes and explores the avenues for innovation to boost their profits. The primary goal is to shed light on how these small enterprises can contribute to the national economic recovery in the aftermath of the pandemic.The study takes place across two Indonesian provinces, East Java and Central Java, spanning three districts: Bojonegoro, Blora, and Klaten. It focuses on the syringe cake makers operating in these regions, examining their innovative approaches, customer appeal, and the economic impact on the involved entrepreneurs. The research methodology employs observation and online interviews conducted through Google Forms.The findings reveal that the syringe cake business in these areas has undergone innovations in various aspects, including flavors, shapes, packaging, and branding. These changes have significantly enhanced the public's interest in syringe cakes, driven by factors such as taste, ingredients, toppings, packaging, brands, and competitive pricing. Most notably, these innovations have led to a considerable increase in the economic income of the mothers engaged in this enterprise. As a result, syringe cakes have emerged as a lifeline for these small businesses, positioning them to play a pivotal role in both the survival of local entrepreneurs and the broader national economic recovery efforts amid and beyond the pandemic. Keywords: Syringes; Innovation; Attractiveness; Economic Income; Small Business; Housewife.